2012
DOI: 10.1161/circulationaha.111.068064
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prognosis of Resistant Hypertension in Hypertensive Patients

Abstract: Background Despite a recent American Heart Association (AHA) consensus statement emphasizing the importance of resistant hypertension, the incidence and prognosis of this condition is largely unknown. Methods and Results This retrospective cohort study in two integrated health plans included patients with incident hypertension started on treatment from 2002–2006. Patients were followed for the development of resistant hypertension based on AHA criteria of uncontrolled blood pressure despite use of three or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
510
6
47

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 806 publications
(610 citation statements)
references
References 28 publications
17
510
6
47
Order By: Relevance
“…3 Data from clinical trials suggest that the prevalence may be substantially higher and the incidence rate among all hypertensive adults has been reported at 1.9 % per year. 4 In 2008, the American Heart Association (AHA) published guidelines for treatment of resistant hypertension that included recommendations for optimal diuretic use (chlorthalidone as the preferred thiazide diuretic), adding an aldosterone antagonist as a fourth medication for uncontrolled BP, and using fixed-dose combination drugs. 3 According to these guidelines, most resistant hypertension patients should be treated with an appropriately dosed thiazide diuretic, calcium channel blocker (CCB), and an ACE inhibitor (ACE-I) or angiotensin receptor blocker (ARB) with aldosterone antagonists as the first choice for patients whose BP remains uncontrolled on optimal doses of ≥ 3 distinct classes of antihypertensive medications.…”
Section: Introductionmentioning
confidence: 99%
“…3 Data from clinical trials suggest that the prevalence may be substantially higher and the incidence rate among all hypertensive adults has been reported at 1.9 % per year. 4 In 2008, the American Heart Association (AHA) published guidelines for treatment of resistant hypertension that included recommendations for optimal diuretic use (chlorthalidone as the preferred thiazide diuretic), adding an aldosterone antagonist as a fourth medication for uncontrolled BP, and using fixed-dose combination drugs. 3 According to these guidelines, most resistant hypertension patients should be treated with an appropriately dosed thiazide diuretic, calcium channel blocker (CCB), and an ACE inhibitor (ACE-I) or angiotensin receptor blocker (ARB) with aldosterone antagonists as the first choice for patients whose BP remains uncontrolled on optimal doses of ≥ 3 distinct classes of antihypertensive medications.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have observed a prevalence of around 12% to 14% of treated hypertensives 2, 3. Compared with subjects with controlled hypertension with 3 or less antihypertensive drugs, patients with RH more frequently have target organ damage4, 5 and a higher incidence of cardiovascular events 6. We have previously reported that more than one third of RH patients have normal 24‐hour BP (white‐coat RH) and they exhibit a better cardiovascular risk profile compared with those with elevated 24‐hour BP 2…”
mentioning
confidence: 99%
“…9 Notably, when the development of CKD was excluded, aTRH was no longer associated with an increased risk for adverse CV outcomes (adjusted hazard ratio 1.18; 95% CI 0.98-1.43, P ¼ .09). 9 Given the known link between BP and adverse CV outcomes, the Kaiser data suggest that either larger or higher risk cohorts of aTRH patients may be necessary to fully uncover the relationship between aTRH and CV outcomes.…”
Section: Atrh and CV Riskmentioning
confidence: 94%
“…More recently, large prospective cohort studies have investigated the incidence and prevalence of aTRH. Daugherty and colleagues 9 examined the incidence of aTRH among patients in the combined Kaiser Northern California and Kaiser Colorado databases. Among 205,750 newly diagnosed hypertensive patients, 1.9% were found to have aTRH, defined as uncontrolled BP on 3 or more antihypertensive medications or controlled BP on 4 or more antihypertensive medications, plus at least 80% medication adherence at 1.5 years of follow-up.…”
Section: Epidemiology Of Atrhmentioning
confidence: 99%
See 1 more Smart Citation